Judicial Reasoning on Asset Forfeiture as the Satisfaction of Substitute Compensation - Hafiz Aulia; Ismansyah Ismansyah; Nani Mulyati (Journal of Progressive Law and Legal Studies, 2026)
The eradication of corruption in Indonesia faces a critical shift from retributive paradigms toward restorative justice and state financial recovery. This research examines Supreme Court Decision No. 4985 K/Pid.Sus/2022, which reflects an anomalous disparity between recovery ethos and procedural positivism. The study analyzes the ratio decidendi underlying the court’s rejection of seized physical assets as restitution and evaluates its strategic implications for the national asset forfeiture architecture. Employing a normative-doctrinal methodology, the analysis draws on Legal Purposivism and Integrative Jurisprudence. Findings reveal that the judiciary’s hyper-formalistic interpretation prioritized mathematical certainty over legal utility, paradoxically returning seized vehicles to the convict. This forced the Prosecution to resort to extra-procedural “bureaucratic gymnastics” to secure the assets, thereby exposing systemic inefficiencies. Macro-statistically, the current conviction-based regime yields a negligible recovery rate relative to the state's absolute losses of IDR 28.4 trillion in 2023. Significantly, this research contributes to criminal law jurisprudence by deconstructing the doctrinal impasse of the conventional in personam framework, providing a robust theoretical foundation for systemic legal reform. It concludes that transitioning to an in rem or Non-Conviction Based Asset Forfeiture mechanism, as mandated by UNCAC Article 54, is an absolute imperative. Accelerating the Asset Forfeiture Bill will transcend rigid procedural dogmatism, ensuring efficient asset recovery and liberating the state from systemic institutional failures.